PRICING IN THE SYSTEM OF TECHNOLOGY TRANSFER - Kosenko V.V.; Milash L.M. (Pressing Problems of Public Administration, 2016)
The article is devoted to the analysis of existing methods of pricingin in the current conditions, inparticular marketing method estimates. The article has revealed the speci cs of forming of prices oninformative goods and services. The modern tendencies of the international technologies transferand the participation of Ukraine are analyzed. It has been proven that pricing system of technologytransfer is formed as a result of cooperation of all market participants.